ASSOCIATIVE MEANINGS OF KISUKUMA-ENGLISH COLOUR TERMS - S. Hussein, Katila; Olenyo Malande, Moses James; Mpobela, Leah; Nestroy, Ligembe (University of Darussalam Gontor, 2024)
The paper analyzes Kisukuma colour terms focusing on associative meanings encoded in colours.Data on colours are analyzed using thematic analysis where they are grouped and organized in eightkisukuma colour terms namely: Yape- white, Yapi- black, Yaza- red, Ndilizu- green Luduhlu/yangayellow, Bhuhulu/bhululu – blue, Matalaka/madaraka- light blue and Yakhu- grey. The studyestablishes that kisukuma colour terms are enriched with different associative meanings which havemore positive than negative meanings in sense that the uses of yapi- black and yaza- red are mostlynegative. In contrast, yape-white colour, luduluh- yellow and ndilizu- green colour mostly havepositive associative meanings, bhuhulu/bhululu- blue, Matalaka/madaraka- light blue and yakhugrey had narrow meanings which were positive.